Trade Cooperation Between China and Indonesia in the Context of Carbon Border Tax: Current Situation and Prospect - Gang , He; Qilin, Zheng; Xin, Yi (Published by Confucius Institute UNS, 2000)
In recent years, China-Indonesia relations have flourished, with trade and investment constantly expanding, showing strong resilience and vitality. However, in the face of profound changes unseen in a century, international challenges emerge one after another. The implementation of a carbon border tax will have a huge impact on international trade, and China and Indonesia will also be affected. This paper reviews the concepts and international progress of carbon border tax. In the context of the carbon border tax, China and Indonesia will meet the challenges and seize the development opportunities, so as to cultivate new driving forces and growth points for cooperation between the two countries, and jointly promote the transformation of international trade into green trade.